Research Institutes in Poland as an Element of the National Innovation System—Complexity, Financing and Effectiveness - Izabela Jonek-Kowalska (Journal of Open Innovation: Technology, Market and Complexity, 2021)
Transfer and diffusion of knowledge and technology is a key condition for the development of innovation. In practice, they take place at the interface between science and business, which makes the level of innovation and development of a given economy depend on the effectiveness and efficiency of universities and other scientific units co-creating the national innovation network. With this important circumstance in mind, this article presents an assessment of the operations of selected research institutes in Poland in 2014–2019 in the context of pro-efficiency statutory changes aimed at making the commercialization of research and development results more effective. The multiple case study used in the article includes five units operating in the field of environmental protection (two) and energy (three)—sectors relevant to the transformation of the national energy sector. The research analyzes the sources of funding of the institutes’ operations, their profitability and the financial effectiveness of their scientific and research staff. The results of the research indicate the adaptability of the surveyed institutes to the new rules of financing and the possibility of their wider than previously opening to business relations, as well as at least partial independence from budget financing. This is a valuable observation from the perspective of shaping innovation policy and the principles of operation of the national innovation system in developing economies.